Municipal wastes management and groundwater contamination processes in South of Córdoba, Argentina - Gomez, Maria Laura (2010)
In Coronel Moldes, Argentina, waste management practices consist in municipal waste being tipped directly onto an area of sand dunes at the municipal waste disposal site (MWDS). Moreover, untreated liquid waste from septic tanks and latrines from urban areas are discharged in the same place. This co-disposal waste management is very common in many regions of Argentina and its impact on the groundwater of Coronel Moldes has not been evaluated. The study area is located in the vicinity of a MWDS in a flatlands environment that is typical of Argentina. The main objective of this study was to evaluate the impacts on groundwater quality of current waste management practices in order to consider the requirement for new guidelines for sustainable groundwater management. Three groundwater monitoring wells were installed up-, across- and down-gradient of the MWDS. The principal aquifer is formed by sandy silt sediments (loess). Groundwater levels in the area of the MWDS are between 5.6 m and 7.8 m. The Vulnerability index indicates that groundwater in this area has a high vulnerability. Groundwater in the vicinity of the MWDS shows elevated electrical conductivity, high concentrations of Cl-, Na+, and HCO3- ions, COD, BOD5 and aerobic bacteria and less dissolved oxygen than the background values indicating the presence of organic matter. Municipal waste management represents a significant omission in current groundwater protection policy at Coronel Moldes. Strict supervision of solid and liquid municipal waste disposal needs to be instigated in order to ensure that the groundwater remains free of contamination and to allow a sustainable environmental management.